IMPACT OF HOSPITAL PHARMACISTS ON THE PAEDIATRIC DISCHARGE PROCESS. Issue 8 (11th July 2014) - Barry, M; Semple, D
Abstract : Aim: To evaluate the discharge planning process undertaken by hospital pharmacists in a paediatric hospital and to identify areas for improvement in the discharge planning process. Method: Accurate and timely medicines information at the point of discharge is essential for continuity of care.1 Studies have been conducted on the role of the pharmacist in the adult discharge planning process but very few studies have been conducted in paediatrics.2 Many of the medicines used for infants and children are not licensed or available readily from community pharmacies. The dosage form of paediatric medicines is usually designed for adult use and may not be "age-appropriate" for a child.3 The pharmacy department contact community pharmacies daily regarding paediatric discharge prescriptions, providing information about the discharge medicines. A few days supply of medicines are commonly dispensed as unlicensed medicines and extemporaneous ingredients are not routinely stocked in community pharmacies. The authors contacted community pharmacies for each occasion a pharmacist was involved in the medication discharge planning process during January 2013. Pharmacists were invited to participate in a telephone survey regarding the discharge information they had recevied from the pharmacy department. They were asked to rate on a 5 point Likert scale the discharge information provided to them and medicine information provided to parents/carers. They were also asked if they had to order an unlicensed medicine or make an extemporaneous preparation or if the parents/carers recevied a patient medication chart. Surveys were entered into an Excel database and analysed. Results: Forty-two community pharmacies were contacted and thirty-four pharmacists agreed to participate in the survey. The percentages of community pharmacies that were either very satisfied or satisfied with ordering details and timeliness of communication provided by the pharmacy department were 76% and 18% respectively. 82% of pharmacists were required to order an unlicensed medicine and 18% of pharmacists were requested to make an extemporaneous preparation. 44% of patients/carers received a patient medication chart. 89% of pharmacists were able to obtain a child's medicines before the supply from OLCHC ran out. Conclusion: The current discharge planning process is ensuring a high level of satisfaction amongst community pharmacies with regards to timeliness and completeness of discharge medication information. Hospital pharmacists can provide accurate and timely information to community pharmacies regarding paediatric discharge prescriptions allowing seamless transfer of patients to the community. It was identified that all patient medication charts should be sent to the community pharmacy as standard practice.